2018
DOI: 10.1016/j.ajpath.2017.09.009
|View full text |Cite
|
Sign up to set email alerts
|

Co-Localization of Insulin-Like Growth Factor Binding Protein-1, Casein Kinase-2β, and Mechanistic Target of Rapamycin in Human Hepatocellular Carcinoma Cells as Demonstrated by Dual Immunofluorescence and in Situ Proximity Ligation Assay

Abstract: Insulin-like growth factor binding protein (IGFBP)-1 influences fetal growth by modifying insulin-like growth factor-I (IGF-I) bioavailability. IGFBP-1 phosphorylation, which markedly increases its affinity for IGF-I, is regulated by mechanistic target of rapamycin (mTOR) and casein kinase (CSNK)-2. However, the underlying molecular mechanisms remain unknown. We examined the cellular localization and potential interactions of IGFBP-1, CSNK-2β, and mTOR as a prerequisite for protein-protein interaction. Analysi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 30 publications
1
14
0
Order By: Relevance
“…Moreover, how the phosphorylation of IGFBP-1 is regulated has, until recently, remained unknown. Based on studies in cultured HepG2 cells and primary fetal baboon hepatocytes, we demonstrated that inhibition of mTOR is required for increased IGFBP-1 secretion and phosphorylation in response to hypoxia [83,84] and the enhanced IGFBP-1 secretion following decreased amino acid availability [85]. In contrast, IGFBP-1 hyperphosphorylation in response to amino acid deprivation is mediated by activation of the AAR signaling pathway [85] (Figure 1).…”
Section: Fetal Liver Mtor and Aar Signaling Pathways Link Oxygen And mentioning
confidence: 98%
See 1 more Smart Citation
“…Moreover, how the phosphorylation of IGFBP-1 is regulated has, until recently, remained unknown. Based on studies in cultured HepG2 cells and primary fetal baboon hepatocytes, we demonstrated that inhibition of mTOR is required for increased IGFBP-1 secretion and phosphorylation in response to hypoxia [83,84] and the enhanced IGFBP-1 secretion following decreased amino acid availability [85]. In contrast, IGFBP-1 hyperphosphorylation in response to amino acid deprivation is mediated by activation of the AAR signaling pathway [85] (Figure 1).…”
Section: Fetal Liver Mtor and Aar Signaling Pathways Link Oxygen And mentioning
confidence: 98%
“…Moreover, it was demonstrated that CK2 and PKC constitute the key kinases, regulated by mTOR and AAR, responsible for IGFBP-1 serine phosphorylation [52,84,87] (Figure 1). An important role of CK2 in the phosphorylation of IGFBP-1 was further supported by extensive co-localization between these two proteins in HepG2 cells ( Figure 2).…”
Section: Fetal Liver Mtor and Aar Signaling Pathways Link Oxygen And mentioning
confidence: 99%
“…When actin filaments are pulled, the R3 domain will undergo a conformational change, which causes RIAM to dissociate and vinculin to bind [7,41]. Talin is a mechanosensitive molecule and this mechanosensitivity relates to the interaction of talin with vinculin [42,43]. Vinculin is a major talin-binding partner that facilitates crosstalk between talin and actin through its talin-binding head domain (V-head) and its actin-binding tail domain (V-tail) [44,45].…”
Section: Discussionmentioning
confidence: 99%
“…The nutrient-sensitive kinase mechanistic target of rapamycin complex 1 (mTORC1) is overactivated in many cancers including HCC (70)(71)(72)(73)(74)(75)(76)(77)(78)(79). Not only insulin and IGF-1 activate mTORC1 but also AAs (80,81), preferentially the BCAAs leucine, isoleucine and valine (82)(83)(84)(85)(86)(87)(88).…”
Section: Bcaasmentioning
confidence: 99%